2022
DOI: 10.1002/smll.202202848
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Integration and Pharmacomechanical Function of Enzyme‐Magnetite Nanoparticle Swarms for Low‐Dose Fast Thrombolysis

Abstract: Magnetic micro‐/nanoparticles are extensively explored over the past decade as active diagnostic/therapeutic agents for minimally invasive medicine. However, sufficient function integration on these miniaturized bodies toward practical applications remains challenging. This work proposes a synergistic strategy via integrating particle functionalization and bioinspired swarming, demonstrated by recombinant tissue plasminogen activator modified magnetite nanoparticles (rtPA‐Fe3O4 NPs) for fast thrombolysis in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 55 publications
0
23
0
1
Order By: Relevance
“…The NPs, manipulated by a customized rotating permanent magnet system, not only achieved targeted thrombolysis of rtPA but also the synergistic rotational motion of the NP cluster enhanced the fluid shear force acting on the thrombus surface; thus, accelerating the dissolution of the thrombus and amplifying the thrombolytic efficacy of the drug ( Figure a,b). [ 84 ] Meanwhile, histological analysis of rabbit carotid artery sections revealed that the mechanical force of this magnetite NP population did not cause damage to the vessel wall and had a high safety and clinical translation potential. In addition, based on Fe 3 O 4 , Prilepskii et al.…”
Section: Application Of Nanotechnology In Thrombosis Therapymentioning
confidence: 99%
See 4 more Smart Citations
“…The NPs, manipulated by a customized rotating permanent magnet system, not only achieved targeted thrombolysis of rtPA but also the synergistic rotational motion of the NP cluster enhanced the fluid shear force acting on the thrombus surface; thus, accelerating the dissolution of the thrombus and amplifying the thrombolytic efficacy of the drug ( Figure a,b). [ 84 ] Meanwhile, histological analysis of rabbit carotid artery sections revealed that the mechanical force of this magnetite NP population did not cause damage to the vessel wall and had a high safety and clinical translation potential. In addition, based on Fe 3 O 4 , Prilepskii et al.…”
Section: Application Of Nanotechnology In Thrombosis Therapymentioning
confidence: 99%
“…Moreover, as the thrombus is located right in the lumen of the blood vessel, drug delivery to it appears to be more convenient than to the tumor and shows larger therapeutic potential. [82] In the last decade, researchers have developed various nanocarriers, including inorganic particles such as mesoporous silica, [72,83] metal NPs, [84] and organic particles including micelles, [85,86] liposomes, [87,88] and polymers. [89,90] By functionally modifying these nanocarriers, it is possible to achieve targeted delivery of thrombotic medicines.…”
Section: Necessity and Significance Of Nanotechnology Interventionmentioning
confidence: 99%
See 3 more Smart Citations